THE SUFFIX WHICH ARE RESULTED WITH ADDITION OF WORDS IN TURKISH - Nadir İLHAN (Fırat University, 2019)
Affixation is the event that the words lose their structural features and become an affix, and the words attached are used in harmony with the words they were added by losing their independent structures. We have learned from our written documents that the existence of some of the affixes in our language system has been used since the old Turkish period in which the first written texts of the Turkish language that have reached today were given. It is also known that some of them appear later, this emergence is not from out the existence but by changing their present forms and functions. Some of the Turkish affixes were initially words, but later they become affixes and formed their present forms. The affixed words in Turkish language are nouns, pronouns, prepositions and auxiliary verbs. The Turkish affixes provided the unity of use, and since they come after the words they were added, they easily became suffixes. Although some of the affixes are out of harmony at the time of affixation, the words formed by affixation are generally compatible with the vowel and consonant harmony.